PLASMA p-tau217 AS A MINIMALLY INVASIVE BIOMARKER FOR ALZHEIMER’S DISEASE DIAGNOSIS: ANALYTICAL PLATFORMS, DIAGNOSTIC PERFORMANCE, AND CLINICAL IMPLEMENTATION CHALLENGES - Oliwia Lenkiewicz; Julia Lenkiewicz; Zuzanna Chmielewska; Marcin Trzciński; Agata Kotłowska; Wiktoria Napiórkowska; Aleksandra Izabela Masłowska; Anna Gwóźdź-Broczkowska; Gabriela Luba (International Journal of Innovative Technologies in Social Science, 2026)
Background: Plasma phosphorylated tau at threonine 217 (p-tau217) has emerged as a promising minimally invasive biomarker for the biological detection of Alzheimer’s disease. This review aimed to evaluate the analytical platforms used for plasma p-tau217 measurement, their diagnostic performance, and the principal challenges associated with its implementation in clinical practice. Methods: A structured narrative review of publications issued between 2019 and 2026 was conducted using PubMed/MEDLINE, Scopus, and Web of Science, with Google Scholar and reference-list screening used as supplementary sources. Studies evaluating plasma p-tau217 assays, analytical validation, diagnostic accuracy, comparison with positron emission tomography or cerebrospinal fluid biomarkers, and clinical implementation were included. Owing to substantial methodological and analytical heterogeneity, findings were synthesised narratively. Results: Plasma p-tau217 showed high diagnostic performance for identifying amyloid and tau pathology and generally outperformed other phosphorylated tau isoforms. Mass-spectrometry-based measurement, particularly percentage p-tau217, demonstrated the highest analytical selectivity and diagnostic accuracy. However, fully automated immunoassays showed greater potential for routine laboratory use because of their higher throughput and reduced technical complexity. Diagnostic performance varied according to the assay, cut-off values, clinical setting, disease prevalence, and patient characteristics. A two-cut-off strategy improved classification while retaining an intermediate group requiring confirmatory testing. Conclusions: Plasma p-tau217 may substantially improve access to biological Alzheimer’s disease diagnostics, but it should not be interpreted as a stand-alone test. Clinical implementation requires assay-specific validation, standardization, external quality control, and integration with clinical assessment and confirmatory diagnostic methods.